2014
DOI: 10.1007/s00784-014-1207-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunodulatory properties of dental pulp stem cells derived from healthy and inflamed teeth

Abstract: SCDIP is not a viable therapeutic cell source especially when used in graft versus host disease (GvHD) and organ rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 35 publications
8
53
1
Order By: Relevance
“…In this study, our results were concurrent with previous reports whereby cells were of fibroblastic phenotype and could be expanded in culture flasks (Yazid et al 2014;Abu Kasim et al 2012;Govindasamy et al 2010a). On top of that SHED were shown to have decent outcome in terms of cell count, PDT as well as senescence assay.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, our results were concurrent with previous reports whereby cells were of fibroblastic phenotype and could be expanded in culture flasks (Yazid et al 2014;Abu Kasim et al 2012;Govindasamy et al 2010a). On top of that SHED were shown to have decent outcome in terms of cell count, PDT as well as senescence assay.…”
Section: Discussionsupporting
confidence: 92%
“…Three-lineage differentiation Mulitipotency of SHED was assessed by differentiating them into adipocytes, chondrocytes, and osteocytes as described previously (Yazid et al 2014;Govindasamy et al 2011). Briefly, adipogenic differentiation was initiated by inducing the cells with 200 mM indomethacin, 0.5 mM 3-isobutyl-1-methyxanthine (IMBX), 10 mg/mL insulin and 1 mM dexamethasone (all reagents from Sigma-Aldrich).…”
Section: Growth Kineticsmentioning
confidence: 99%
“…Yazid et al reported that MSCs derived from inflamed pulp deciduous tissues were highly dysfunctional in MSC characteristics, stemness, and immunomodulatory properties [17]. In contrast, our results showed that there were no significant differences between SCIDs and SHEDs in their in vitro proliferation and multidifferentiation potentials.…”
Section: Discussioncontrasting
confidence: 79%
“…Key and well-characterized cytokines, including IL-1a, IL-1b, TNF-a, IL-4, IL-6, IL-8, and IL-10, are highly expressed by structural cells from pulp tissue, such as odontoblasts, fibroblasts and mesenchymal stem cells, along with immune cells, when they are exposed to bacterial and dental materials components. [24][25][26][27][28] These molecules play regulatory functions for lymphocytes, macrophages, and neutrophils, activating the inflammatory cascade, 29,30 which may result in release of proteolytic enzymes, such as metalloproteinases, with the consequent disruption of extracellular matrix components. 31,32 Prostaglandin E 2 , synthesized by COX-2 gene is also a major pro-inflammatory mediator, which is known to accelerate inflammation and injury in several tissues, including the dental pulp.…”
Section: Discussionmentioning
confidence: 99%